Laboratory breeding and testing of Australorbis glabratus for molluscicidal screening - Hopf, H. S. (1962)
The authors describe a technique for laboratory breeding of Australorbis glabratus, the intermediate host of Schistosoma mansoni in South America. This technique is suitable for obtaining large numbers of snails in a small space with the minimum of maintenance time and under carefully controlled conditions. Techniques are also outlined for testing molluscicides against eggs and young snails as well as against adults. It is considered that, in view of the saving in breeding time and space effected, testing against young snails has several advantages for primary screening. With no compounds tested have anomalous results been obtained. Finally, the authors report on the results obtained with a new class of molluscicidal compounds—the organo-tins—which cause snail mortality in concentrations as low as those of any of the other molluscicides tested.